2019
DOI: 10.1038/s41598-019-45642-w
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling and identification of let-7a as a target to prevent chemotherapy-induced primordial follicles apoptosis in mouse ovaries

Abstract: Cancer treatments as cyclophosphamide and its active metabolites are highly gonadotoxic leading to follicle apoptosis and depletion. Considering the risk of subsequent infertility, fertility preservation is recommended. Beside the germ cells and gametes cryopreservation options, ovarian pharmacological protection during treatment appears to be very attractive. Meanwhile, the advances in the field of oncology have brought microRNAs into spotlight as a potential feature of cancer treatment. Herein, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…In our previous study, we showed that miRNAs can alter their expression profile due to chemotherapy exposure, and this change can be observed after short exposure during 1 h at 20 µM (1 h/4-HC/20 µM) or long exposure during 24 h (24 h/4-HC/20 µM) (Figure 1a) [32]. Amongst the most affected miRNAs, which changed their expression levels after 1 h of exposure to 4-HC in mouse postnatal-day 3 (PND3) ovaries, the miR-10a was one of the most downregulated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we showed that miRNAs can alter their expression profile due to chemotherapy exposure, and this change can be observed after short exposure during 1 h at 20 µM (1 h/4-HC/20 µM) or long exposure during 24 h (24 h/4-HC/20 µM) (Figure 1a) [32]. Amongst the most affected miRNAs, which changed their expression levels after 1 h of exposure to 4-HC in mouse postnatal-day 3 (PND3) ovaries, the miR-10a was one of the most downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…The transfection of PND3 ovaries in vitro was performed using Lipofectamine RNAiMAX, a liposome-based delivery system (Figure 2a). In our previous study, a transfection protocol was developed after testing different concentrations of the Lipofectamine and the mimic miRNA molecules, while the transfection’s efficiency was verified by a fluorescent label dsRNA [32]. After 48 h in culture with the transfection mix (Lipofectamine + Alexafluor labeled dsRNA), the fluorescent signal was detected in every ovarian section, indicating that the transfection is successful (data is not shown).…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs can be effective techniques as their expression can be adjusted with their microenvironment during chemotherapy treatment, thus minimising off-target toxicity. Lethal 7 (let-7a) mimic is an example of a new miRNA based therapeutic to minimise follicle injury following chemotherapy treatment [170]. However, this work is at an early stage, with challenges including how to deliver miRNAs to a specific target organ with minimum side effects.…”
Section: Discussionmentioning
confidence: 99%
“…These data may pave the way for future studies aimed to optimise the conditions for in vitro maturation of frozen-thawed testicular tissue for future use in fertility preservation strategies. Alternatively, less invasive methods are also in the experimental phase of development such as the administration of cytoprotective agent concomitantly to cancer treatment regimen or the miRNA replacement approaches to prevent chemotherapeutic damages [57,92,[166][167][168][169].…”
Section: Discussionmentioning
confidence: 99%